Effect of 4PU-30 on leaf senescence and active oxygen metabolism in rice - ZHU Cheng; ZENG Guang-wen (浙江大学学报. 农业与生命科学版)
Effect of 4PU-30［N- phenyl- N′- (2-chloro-4-pyridyl) urea］on leaf senescence and active oxygen metabolism in rice were investigated. The detached leaf sections of 2 cm in length were floated on the solution of 4PU-30 at the concentration of 10-3-101 mg/L respectively and kept in darkness at 20 ℃. The result showed that 4PU-30 at the various concentrations significantly decreased the degradation of cholorphyll and protein, retarded the process of leaf senescence. Rice plants were sprayed with 4PU-30 (100 mg/L) at flowering stage after heading at one week interval for 3 times, 4PU-30 also retarded the process of senescence of intact leaves. The study also revealed that the activities of both superoxide dismutase (SOD) and catalase (CAT) were retarded, the levels of super oxygen-free radical (<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/1008-9209-2000-05-0483-I002.jpg"/>) and malonaldehyde (MDA) were significantly declined by 4PU- 30 in detached leaves or intact leaves. It was suggested that the physiological basis of 4PU- 30 in delaying leaf senescence was to regulate directly or indireactly activate oxygen metabolism.